THE ROLE OF CULTURAL HERITAGE SITES IN THE DEVELOPMENT OF THE TOURISM INDUSTRY - Islom Ilgor ugli Fattoyev (Western European Studies, 2025)
This article provides a scientific and theoretical analysis of the role of cultural heritage sites in the development of the tourism industry. The importance of cultural heritage in enhancing tourism infrastructure, increasing regional economic potential, and promoting national values is examined. The study explores the effective use of historical monuments and cultural heritage sites in tourism and proposes recommendations for their preservation and integration into the tourism sector
Keywords: tourism; cultural heritage; historical monuments